2006
DOI: 10.1111/j.1753-4887.2006.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidence of Interventions Using the Mediterranean Diet: A Systematic Review

Abstract: The Mediterranean Diet has been associated with greater longevity and quality of life in epidemiological studies, the majority being observational. The application of evidence-based medicine to the area of public health nutrition involves the necessity of developing clinical trials and systematic reviews to develop sound recommendations. The purpose of this study was to analyze and review the experimental studies on Mediterranean diet and disease prevention. A systematic review was made and a total of 43 artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
227
0
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(249 citation statements)
references
References 60 publications
4
227
0
13
Order By: Relevance
“…No other comparable study was found with obese patients. However, similar findings have been described in several studies in patients with cardiovascular diseases (Serra-Majem et al 2006).…”
Section: Dietary Counsellingsupporting
confidence: 62%
“…No other comparable study was found with obese patients. However, similar findings have been described in several studies in patients with cardiovascular diseases (Serra-Majem et al 2006).…”
Section: Dietary Counsellingsupporting
confidence: 62%
“…22 The most recent systematic reviews of cross-sectional, prospective cohort, and intervention studies have demonstrated further the favorable effects of a Mediterraneanstyle dietary pattern, 23 in terms of both a reduction in cardiovascular events 24 and improvements in many traditional CVD risk factors, including blood lipids/lipoproteins, body weight and BMI, SBP and DBP, fasting glucose and insulin resistance, and C-reactive protein. 25,26 In addition to the epidemiologic evidence, numerous short-term intervention trials have evaluated the effects of a Mediterranean-style diet on CVD risk factors ( Table 2). These trials provide additional evidence for the beneficial effects of a Mediterranean-style dietary pattern on the following CVD risk factors: plasma lipid/lipoprotein profiles, 27-31 apolipoproteins, 28 body weight/composition, 29,32,33 oxidative stress, 34 glycemic response, 27,29,32,33 inflammatory markers, 28,29 vascular function, 29,[35][36][37][38] and criteria for metabolic syndrome.…”
Section: Mediterranean Diet: Overview and Evidence Basementioning
confidence: 99%
“…Nutrient studies, epidemiologic studies, and clinical trials indicate that the Mediterranean diet lowers the risk of chronic disease [8,9]. Accordingly, it is widely recommended as a healthy dietary pattern model to improve the quality of life [10,11].…”
Section: Introductionmentioning
confidence: 99%